Medicalização na educação: sentidos de professoras e de uma psicóloga que atua na área educacional - Santos, Caio Cesar Portella (2015)
This study aim to investigate the senses attributed of elementary public school teachers and an educational psychologist about the medicalization problem during the educational process and sought to understand the referral process and assessment of students with suspected learning disorders in the city of Bauru. The study was based in a survey answered by a regular teacher, a teacher for special students and an educational psychologist. The survey was guided by the Historical-Cultural Theory and involved semi-structured interviews, participant observation and records in the field diaries. The results indicated that: a) there is a systematization of the referral process that includes school internal procedures, involving the regular teacher and the teacher for special students, preceding the referral of children with learning disorders for the specialized institutions contracted by the local government; b) there is a great disproportion in public schools between the diagnoses related to school problems when compared to all other possible diagnoses in the field of Special Education, indicating that most of the diagnoses in school are inconclusive or pointing unspecified disorders; c) the reasons highlighted by the participants for the referral of students covered aspects such as lack of attention; disinterest; hyperactivity and difficulties in reading and writing; d) the participants considered that family education contributes to the occurrence of school failure, especially regarding lack of support and the settlement of limits by the parents; e) professional interviewed consider that in certain situations the use of medication is necessary, such as ADHD, regardless the school context and educational activities proposed. We emphasize the need to know how referrals and diagnoses are produced as well as the meanings constructed by the professionals involved in the process in order to discuss them. Finally, we discuss the importance of critically analyze the multiple factors related to school complaints, in order to overcome reductionist views that tend to pathologization and blame the children for not learn in school.